Aerodynamic Control System for a Deployable Re-entry Capsule. (April 2021) - Fedele, Alberto; Carannante, Salvatore; Grassi, Michele; Savino, Raffaele
Abstract: Deployable aerobrakes for Earth re-entry capsules may offer many advantages in the near future, including the opportunity to recover on Earth payloads and samples from Space with reduced risks and costs with respect to conventional systems. Such capsules can be accommodated in the selected launcher in folded configuration, optimizing the available volume, and when foreseen by the mission profile the aerobrake can be deployed in order to increase the surface exposed to the hypersonic flow and therefore to reduce the ballistic parameter. The ballistic parameter reduction offers as main advantage the opportunity to perform an atmospheric re-entry with reduced aerothermal and mechanical loads. It makes also possible the use of relatively lightweight and cheap thermal protection materials. There are plenty of algorithms and control methods for classical re-entry capsules, such as the Orion and Soyuz re-entry modules. However, a lot of attention is now paid towards how to control low ballistic coefficient capsules with inflatable and mechanically deployable heat shield. The aim of this study is to prove the feasibility of an aerodynamic control system, applied to a mechanically deployable re-entry capsule, in order to increase landing precision at the targeted site. The deployable heat shield is equipped with an actuation system, consisting of eight aerodynamic surfaces, referred to as flaps. The assumed control strategy is to deflect the flaps independently, in order to trim the capsule and produce enough lift and side force to give downrange and cross range maneuverability during the re-entry phase. A control algorithm was developed, implemented and tested in a 3DOF simulation environment. Capsule performances both for uncontrolled ballistic re-entries and for controlled lift re-entries starting from a low Earth orbit have been assessed, verifying the capability of the controller in guiding the capsule toward the chosen target. Monte Carlo simulations were run assuming errors and uncertainties at the de-orbit burn, and the control system has been proved to obtain good results in reducing dispersions at the landing site. Highlights: The aim of this study is to prove the feasibility of an aerodynamic control system. The objective is to increase landing precision of a deployable capsule. The capsule is equipped with eight aerodynamic surfaces. The independent surface deflection is used to trim the capsule. This is used to give downrange and cross range maneuverability.